Past creeds and present formula at the Council of Chalcedon - Hall, Stuart George (Studies in church history, 1997)
The Formula by which the Council of Chalcedon in 451 defined the Person of Christ is a classic case of the deliberate adjustment and interpretation of the past to suit a present need. The assembled bishops at their fifth session gave their assent to a document which not merely prescribed a theological position in the face of the doctrines of Eutyches and Nestorius, but justified doing so in the face of historically-based objections to the enterprise.